2008
DOI: 10.1111/j.1365-2249.2008.03588.x
|View full text |Cite
|
Sign up to set email alerts
|

The Wistar Bonn Kobori rat, a unique animal model for autoimmune pancreatitis with extrapancreatic exocrinopathy

Abstract: SummaryThe male Wistar Bonn/Kobori (WBN/Kob) rat is known to be a unique animal model for chronic pancreatitis with widely distributed fibrosis and degeneration of parenchyma because of the infiltration of lymphocytes. In this report, we show that female (but not male) rats develop dacryoadenitis at 3 months of age, and that both male and female WBN/Kob rats develop sialoadenitis, thyroiditis, sclerotic cholangitis and tubulointerstitial nephritis over 18 months of age. The infiltration of CD8 + cells and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…In contrast to males, female rats of this strain do not show pancreatitis. Sakaguchi et al reported that female rats develop dacryoadenitis at 3 months of age, and that both male and female WBN/Kob rats develop sialoadenitis, thyroiditis, sclerotic cholangitis, and tubulointerstitial nephritis over 18 months of age [24]. These features were observed in autoimmune pancreatitis and autoimmune disease [24].…”
mentioning
confidence: 84%
“…In contrast to males, female rats of this strain do not show pancreatitis. Sakaguchi et al reported that female rats develop dacryoadenitis at 3 months of age, and that both male and female WBN/Kob rats develop sialoadenitis, thyroiditis, sclerotic cholangitis, and tubulointerstitial nephritis over 18 months of age [24]. These features were observed in autoimmune pancreatitis and autoimmune disease [24].…”
mentioning
confidence: 84%
“…[28][29][30][31] To date, several animal models of AIP have been reported. [31][32][33][34][35] In most models, the AIP-like disease is induced by the adoptive transfer of autoreactive cells and self-antigens such as CA-II and LF. Similarly, the adaptive transfer of E. coli-inoculated mice spleen cells to RAG2 À/À mice also reproduced AIP-like pancreatitis in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous report demonstrated that WBN/Kob rats develop daxryoadenitis, sialoadenitis, thyroiditis, sclerotic cholangitis and tubulointerstitial nephritis, and is a useful animal model for AIP and Sjögren-like syndrome in humans. IBM-BMT has been shown to prevent these ADs in this animal model [12]. However, IBM-BMT has a long way to go before an effective standard regimen of AD therapy for patients has been developed.…”
Section: Aip Treated With Ibm-bmtmentioning
confidence: 90%
“…Allogenic Hematopoietic Stem Cell (HSC) transplantation has been shown to be a relatively successful treatment for experimental ADs, and there are a number of reports of Bone Marrow Transplantation (BMT) being used to treat ADs in various mice [3][4][5][6][7][8][9][10]. For example, the following were all resolved after BMT: Insulin-Dependent Diabetes Mellitus (IDDM), in which beta cells are destroyed by the immune system; Rheumatoid arthritis (RA), which primarily attacks the synovial joints; Systemic Lupus Erythematosus (SLE), which is a chronic auto-inflammatory disease of unknown etiology; Multiple Sclerosis (MS), which affects the brain and the central nervous system, and Autoimmune Pancreatitis (AIP), which produces pancreatic masses and ductal strictures [11,12]. ADs show abnormal autoimmune responses by auto-antibodies and T-cell responses to self-molecules in pathological conditions [13].…”
Section: Introductionmentioning
confidence: 99%